The effect of filter cakes enriched with soluble phosphorus used as a fertilizer on the sugarcane ratoons - Santos, Diego Henriques; Silva, Marcelo Almeida; Tiritan, Carlos Sérgio; Crusciol, Carlos Alexandre Costa (Acta Scientiarum. Agronomy, 2014)
The objective of this work was to evaluate the effect of fertilization with filter cakes enriched with soluble phosphate on sugarcane ratoons. The experiment was performed from November 2007 to December 2009 at Presidente Prudente, São Paulo State, Brazil, in a completely randomized block design in a 4 x 4 factorial arrangement, with the first factor consisting of doses of filter cake (0; 1; 2 and 4 mg ha-1) and the second doses consisting of phosphorus fertilizer (0, 50, 100, 200 kg ha-1 of P2O5) with 4 replicates. The following variables were evaluated: the number of tillers per meter, the leaf area index, soluble solids (ºBrix), stalk and sugar yield in the second crop cycle. We found a residual effect in the sugarcane ratoon after applying filter cakes enriched with soluble phosphate in the planting furrow. The initial tillering, leaf area index, stalk and sugar yield in the cane ratoon benefit from the application of filter cakes and soluble phosphate in the planting furrow. The best combination is filter cakes at a dose between 1.0 and 2.0 mg ha-1 with 100 to 200 kg ha-1 soluble phosphate applied at planting. This method obtains higher stalk and sugar yields for sugarcane ratoons.